Qualität rettungsdienstlicher Verdachtsdiagnosen und Dringlichkeitsbeurteilungen: Eine sektorübergreifende, monozentrische Evaluation rettungsdienstlicher IVENA-Verdachtsdiagnosen und IVENA-Sichtungskategorien mit klinischen Daten - Villis, Marten; Henke, Thomas J.; Thate, Stefan; Christoph, Jan; Seeger, Insa (Notfall und Rettungsmedizin, 2024)
Background and objective: The quality of suspected diagnoses and initial assessments made by paramedics without the involvement of emergency physicians is poorly researched. The aim of this study is to evaluate the accuracy of these parameters with and without emergency physician involvement regarding their correlation with clinical data. Methods: This study is a retrospective analysis in which randomly sampled data from the paramedic IVENA eHealth system (suspected diagnosis, initial assessment) from 2019 were compared to clinical data (physician’s diagnosis, outpatient or inpatient treatment) from the emergency department of a hospital in Oldenburg (Evangelisches Krankenhaus Oldenburg, EVK) using crosstabs and logistic regression. Results: A random sample of 1150 cases was drawn from 8443 IVENA registrations for the EVK in 2019. Of these, 978 (85.0%) could be included in the analysis of the suspected diagnoses. Whereas 784 (82.1%) of the paramedics’ suspected diagnosis were fully or partially congruent with the clinical diagnosis, in 150 (15.7%) cases the suspected diagnosis was not confirmed and in 20 (2.1%) cases important symptoms/injuries had been overlooked. The patients most at risk of receiving a false diagnosis were nursing home residents (n = 28, 31.5%; p < 0.001) and people with a suspected neurological diagnosis (n = 76, 28.9%; p < 0.001). In 1005 (87.3%) cases, information regarding the triage category was provided. Of these cases, the paramedics’ triage category matched the care provided (outpatient/inpatient treatment) in 714 (71.0%) cases. In 243 (24.2%) cases the amount of care needed was overestimated and in 48 (4.8%) it was underestimated. Conclusion: Our study shows the need for improvement regarding paramedical quality management. An IT-based feedback system could provide appropriate aid.
CRIS-Team Scopus Importer:2024-11-22
Keywords: Emergency department; Feedback system; Paramedics; Prehospital emergency medicine; Quality assurance